Effectiveness of cognitive-behavioral therapy on sexual function and sexual self-efficacy in pregnant women: An RCT - Mina Nezamnia; Mina Iravani; Mehdi Sayah Bargard; Mahmood Latify (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Cognitive-behavioral therapy (CBT) is one of the ways to improve an undesirable sexual function. Objective: The purpose of this study was to investigate the effect of CBT on the sexual function and sexual self-efficacy of pregnant women. Materials and Methods: In this randomized clinical trial, 36 pregnant women referred to five healthcare centers in Ahvaz, Iran, from December 2016 to January 2017 were enrolled through stratified random sampling in two groups. The case group received counseling based on cognitive behavioral therapy for eight consecutive weeks and the control group received the routine training provided by healthcare staff. Two and four weeks after the end of sessions, both groups completed the Female Sexual Function Index and self-efficacy questionnaires again. Results: The mean of sexual function and self-efficacy scores in pregnant women in the case and control groups before the intervention did not show a significant difference (p = 0.56). The mean of sexual function and self-efficacy scores of pregnant women in the case and control groups was statistically significant two and four weeks, respectively, after the intervention (p ≤ 0.0001). Conclusion: The results of this study showed that counseling based on CBT in comparison with the routine training during pregnancy improves the sexual performance and self-efficacy of pregnant women.